Menelisik Pengelolaan Human Capital di Dunia Bisnis dalam Era New Normal: Studi Kasus pada Generasi Milenial di Bali - Desak Made Diah Prama Yanti; I Gede Sanica (Jurnal Maksipreneur, 2021)
This study analyzes strategies that can be used in managing human capital in the millennial generation in the current new normal era and to find out the supporting and inhibiting factors in managing human capital during the covid-19 pandemic. The research method used is a qualitative research method with a case study model approach. The research location is in Denpasar City, Bali Province. The selection of informants used the purposive sampling technique by determining four companies from various fields as informants, namely Garment, Vila, Cargo, and University. Data in this study analyzes the results of observations, interviews, and documentation obtained. Data analysis uses source triangulation through four stages: data collection, data reduction, data presentation, and drawing conclusions or verification. The study results stated that the human capital management strategy for millennial employees in the new normal era had been affected on two sides. First, from the company side were the COVID-19 pandemic had an impact on decreasing company income and reducing operational activities. For this reason, changes are made, such as dividing work schedules and hours. Employee work, distribution of the rolling system, some employees work from home (WFH), and maximize employee skills into multitasking. Meanwhile, from the employee's perspective, it impacts the income of the employee, where employees receive a much-reduced salary or income, even if they are dismissed at any time to reduce operational costs.